Characterization of coal ash. - Nakagawa, K.; Yamada, K.; Tsurue, T.; Takeda, S.; Ishizaki, K.; Quilao, T.A.; Balais, W.A.; Herrera, A.B.; Pugal, D.L.; Bion, H.H.; Magpantay, C.G.; Abarquez, F.I.; et al.
Coal ash samples were taken from Calaca, Thermal Power Plant in Batangas in 1993 and in 1996. These coal ash samples were screened into different particle sizes. Each particle size was analyzed for its moisture content, amount of unreacted carbon, mineral content and its fusibility. The effect of the different particle sizes on the ash fusibility was investigated. This is a sequel to a study conducted by Pugal, D.L. et al (1995). Results of the characterization show that sieving coal ash samples into different particle sizes give higher sintering, softening and melting temperatures. Big particle sizes also have higher sintering, softening and melting temperatures than the smaller particle sizes.
Keywords: Coal ash -- Philippines (Batangas)